2017
DOI: 10.4274/tjps.99609
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Evaluation of the Toxicity of Cobalt Ferrite Nanoparticles in Kidney Cell

Abstract: ÖZAmaç: Sert manyetik kobalt ferrit nanopartiküllerinin (CoFe 2 O 4 -NP) dikkate değer özellikleri ve fizikokimyasal kararlılıkları farklı endüstri ve tıp alanlarında çeşitli uygulamalarda kullanılmalarına yol açmaktadır. CoFe 2 O 4 -NP'lerin bazı toksik etkilere neden olduğu bildirilmiş olsa da böbrek üzerindeki etkileri hakkında ciddi bilgi eksikliği vardır. Bu çalışmada, CoFe 2 O 4 -NPs'lerinin NRK-52E böbrek hücreleri üzerine toksik etki potansiyellerinin araştırılması amaçlanmıştır. Gereç ve Yöntemler: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Therefore, we were not surprised to find no obvious abnormalities in the ultrastructure of MSCs or changes in the morphology of the tissues studied in the control mice. At present, however, knowledge about the effects of nanomaterials on human (stem) cells is still sparse and contradictory [ 23 , 24 ]. There are some reports of a possible effect of NPs (including cobalt ferrite NPs) on the enzyme activity and cell structure of MSCs, and large differences in responses to NPs have been reported between different cell types, NP concentrations, and exposure times [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we were not surprised to find no obvious abnormalities in the ultrastructure of MSCs or changes in the morphology of the tissues studied in the control mice. At present, however, knowledge about the effects of nanomaterials on human (stem) cells is still sparse and contradictory [ 23 , 24 ]. There are some reports of a possible effect of NPs (including cobalt ferrite NPs) on the enzyme activity and cell structure of MSCs, and large differences in responses to NPs have been reported between different cell types, NP concentrations, and exposure times [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 306,307 ] Cobalt ferrite has shown adverse effects in the zebrafish circulatory system and urinary model NRK‐52E cells. [ 296,308 ] These MNPs can cause unstable heart rate, oedema and DNA damage. [ 296,308 ] In animal models or in vitro cell models, superparamagnetic nanoparticles do the most damage to the nervous system.…”
Section: Toxicity Of Mnpsmentioning
confidence: 99%
“…[ 296,308 ] These MNPs can cause unstable heart rate, oedema and DNA damage. [ 296,308 ] In animal models or in vitro cell models, superparamagnetic nanoparticles do the most damage to the nervous system. [ 295 ] They result in limited ocular toxicity in Sprague‐Dawley rat models, necrosis in EC5v cell lines and hearing displacement in albino guinea pigs.…”
Section: Toxicity Of Mnpsmentioning
confidence: 99%
“…Bossi et al [28] showed that cobalt oxide (Co 3 O 4 ) below 50 nm can migrate into the cell plasma and it is not dependent on the endocytosis pathway. While this is a convenient feature for drug delivery, it can lead to increased cellular toxicity, as shown on kidney cell DNA for cobalt ferrite particles with a rough size of 40 nm in concentrations below 100 µg/mL [29]. Pure cobalt nanoparticles of about 50 nm can also inhibit mRNA and protein expression and even alter cell morphology [30].…”
Section: Viabilitymentioning
confidence: 99%